Pediatric allergy principles and practice - Leung, Donald Y. M., 1949- (Saunders ; Elsevier Health Sciences [distributor], 2011)
Pediatric Allergy supplies the comprehensive guidance you need to diagnose, manage, and treat virtually any type of allergy seen in children. Drs. Leung, Sampson, Geha, and Szefler present the new full-color second edition, with coverage of the diagnosis and management of anaphylaxis, the immune mechanisms underlying allergic disease, the latest diagnostic tests, and more⁵in print and online at expertconsult.com. Treat the full range of pediatric allergic and immunologic diseases through clinically focused coverage relevant to both allergists and pediatricians. Understand the care and treatment of pediatric patients thanks to clinical pearls discussing the best approaches. Easily refer to appendices that list common food allergies and autoantibodies in autoimmune diseases.